Scottish theatre since the seventies - Stevenson, Randall; Wallace, Gavin (Edinburgh University Press, 1996)
This is the first guide to the new Scottish theatre, its people, its politics, its companies and its audiences. Topical and often contentious, this book shows that drama deserves a central place in the current renaissance of Scottish literary culture.